2012
DOI: 10.1136/oemed-2011-100294
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of hand eczema among Danish hairdressing apprentices: an intervention study

Abstract: We were able to increase the use of gloves and reduce the incidence of hand eczema in hairdressing apprentices by implementing a training program in hairdressing schools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
82
1
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(94 citation statements)
references
References 49 publications
7
82
1
4
Order By: Relevance
“…TEWL levels did not differ between apprentices without skin problems, with a history of self-reported skin symptoms, and with objectively present skin symptoms. The only significant predictor of high TEWL levels on the hands was frequent daily hand washing, and this parameter was also related to self-reported skin symptoms and dry skin, confirming the importance of wet conditions for the development of skin changes (8,14). In this study, TEWL levels should be interpreted with caution, owing to the variable and high ambient temperature in the school rooms during measurements, which can affect the TEWL results (26).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…TEWL levels did not differ between apprentices without skin problems, with a history of self-reported skin symptoms, and with objectively present skin symptoms. The only significant predictor of high TEWL levels on the hands was frequent daily hand washing, and this parameter was also related to self-reported skin symptoms and dry skin, confirming the importance of wet conditions for the development of skin changes (8,14). In this study, TEWL levels should be interpreted with caution, owing to the variable and high ambient temperature in the school rooms during measurements, which can affect the TEWL results (26).…”
Section: Discussionsupporting
confidence: 55%
“…The majority of apprentices (91%) reported wearing protective gloves while dyeing hair, but a much smaller number of them reported wearing gloves for rinsing dye from the hair (45%) or for just washing the hair (4%). Similarly, hairdressing apprentices in the United Kingdom and Australia rarely wear gloves for washing hair (9% and 6.3%, respectively) (11,12), whereas the results for German and Danish apprentices are quite different (18.5% and 29.6-46.3%, respectively) (13,14). Our results are the worst in this list, suggesting poor knowledge and awareness of Croatian hairdressing apprentices, and probably their vocational teachers and tutors, regarding the irritant effects of wet work on skin and how it can be prevented by the use of protective gloves.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The authors suggested that this could be interpreted as a healthy worker effect among the young hairdressers. An intervention study educating teachers in vocational schools in skin physiology, allergy and skin protection showed significantly reduced hand eczema among the hairdressers in the intervention group (Bregnhøj et al, 2012). Another paper evaluated the association between exposures to chemical products and airway symptoms such as wheezing and runny nose among young hairdressers in Norway.…”
Section: Discussionmentioning
confidence: 99%
“…One study evaluated the effect of special training in skin protection among hairdressing apprentices (Bregnhøj et al, 2012), while another evaluated the effect of an educational program on skin protection among nursing auxiliary students (Held et al, 2001). They both showed positive effects on the development of skin reactions and hand eczema.…”
Section: Discussionmentioning
confidence: 99%